The Effect of Virtual Reality Technology in Teaching Mathematics on Students’ Ability to Process Data and Graphic Representation - Alzoubi, Khaled Ahmed Aqeel (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The study focused on the impact of using augmented reality (AR) in teaching mathematics to tenth-grade students in the 2022–2023 academic year. The sample consisted of 70 students from schools in the city of Amman, who were divided into 35 students in the experimental group and 35 students in the control group. The researcher utilized the quasi-experimental method and collected data through questionnaires and testing tools. Data were statistically analyzed using the MANOVA test, outcome analysis techniques, and GLM test. The results indicate the quality of virtual reality (VR). Students’ ability to process data improved by 94% in the experimental group and 88% in the control group. The experimental group demonstrated an effective contribution of 97% in improving graphic representation ability, while the control group showed a contribution of 92%. The study relied on the descriptive-analytical method. The study concluded that AR technology and its usage have become largely dependent on preparing technical and material requirements. It also highlighted that this technology aids students in learning scientific facts, concepts, and instructions in an easy and effective manner. The results indicate the necessity of expanding scientific research and studies on the advantages and disadvantages of AR technology and its optimal utilization.